The Effectiveness of Project-Based Learning on Early Childhood Problem-Solving Skills: An Experimental Study - Fatiya; Hayati, Nur (International Journal of Education and Teaching Zone, 2025)
Problem-solving skills are important to be stimulated early on. Problem-solving skills can be stimulated through project learning activities. This study aims to determine the effectiveness of project-based learning on the problem-solving ability of Group B children at TKIT Salman Al Faris I. This type of research is quantitative, and the research design used is the Group Pretest-Posttest Design, with a population of 45 children and a sample of 20 children. The sampling technique employed was purposive sampling, and data collection methods included tests, documentation, and observation. Data analysis involved testing the research hypothesis using a t-test. The results showed that the project learning treatment was effective in improving problem-solving ability. These results were obtained from the pre-test, which had an average value of 65, and the post-test results after treatment had an average of 106, with a minimum gain of 30 points and a maximum value of 120 points. Then, the results of the project learning on problem-solving ability obtained a significant value of 0.000, which indicates a statistically significant value. 0.000 < 0.05 (2-tailed). Having the ability to solve problems will help children to become quality resources. This research demonstrates that project-based learning is effective in enhancing Group B’s problem-solving skills at TKIT Salman Al Faris I.